Transforming microfinance institutions : - Ledgerwood, Joanna (The World Bank, 2006)
In response to a clear need by low-income people to gain access to the full range of financial services including savings, a growing number of microfinance NGOs are seeking guidelines to transform from credit-focused microfinance organizations to regulated deposit-taking financial intermediaries. In response to this trend, this book presents a practical "how-to" manual for MFIs to develop the capacity to become licensed and regulated to mobilize deposits from the public.